PENGARUH KEGIATAN EKSTRAKURIKULER SENI RUPA TERHADAP KREATIVITAS SISWA PADA PEMBELAJARAN KELAS 3 DI MADRASAH IBTIDAIYAH - Hibran Alwi Zaeni; Riva Amelia Ramadhani; Sri Jumini (CV. Adiba Aisha Amira, 2025)
Extracurricular activities are activities carried out as a platform for developing students potential, interests, and talents, conducted outside of school hours. The use of time outside regular school hours provides flexibility for students to participate in these activities maximally without disrupting formal learning processes in the classroom. One form of extracurricular activity that becomes a focus in many elementary schools or madrasah ibtidaiyah is the arts. Artistic activities encompass various branches, such as music, dance, and visual arts, each offering unique benefits in supporting students' development. Visual arts, for example, not only teach skills like drawing or painting but also train students to think creatively, explore new ideas, and improve their ability to express themselves. Additionally, visual arts can shape positive character traits such as discipline, confidence, teamwork, and perseverance. This study aims to explore the influence of extracurricular visual arts activities on the creativity and learning enthusiasm of third-grade students at Madrasah Ibtidaiyah Muhammadiyah Kecepit, Banjarnegara Regency. The approach used in this research is qualitative, employing a case study method that relies on data collection techniques such as direct observation of the activities, in-depth interviews with students and teachers, and documentation of the visual arts activities performed by students. The results of the study show that student participation in extracurricular visual arts activities has a significant impact on their creativity development. Students who were previously passive or unfocused during classroom learning began to show greater interest and enthusiasm when involved in artistic activities. They not only channel their creative ideas but also demonstrate improvements in concentration, responsibility, and enthusiasm for learning in class. Furthermore, these activities create a more enjoyable learning atmosphere, motivating students to engage more actively in formal learning processes. With the various benefits experienced, extracurricular visual arts activities have proven to be an effective strategy in supporting the comprehensive development of students' potential, both academically and non-academically, while enriching their learning experience in school. Therefore, it is essential for schools to continuously promote and manage extracurricular visual arts activities consistently as part of efforts to improve the quality of education.